High-Pressure Processing (HPP) Energy Efficiency and Scalability Challenges in Ultra-Processed Meat: A Review (Journal of Clean Technology, 2025)
The global expansion of ultra-processed meat products (e.g., sausages, nuggets) faces dual challenges: microbiological safety risks from conventional thermal processing and rising consumer demand for clean-label, nutritious options. High-Pressure Processing (HPP) emerges as a promising non-thermal technology to address these concerns by inactivating pathogens while preserving sensory and nutritional quality. However, its industrial adoption is hindered by significant energy efficiency and scalability constraints. This systematic literature review synthesizes recent research to critically analyze these barriers. Methodologically, we conducted a Systematic Literature Review (SLR) using databases such as Scopus, ScienceDirect, Web of Science, and PubMed, focusing on studies related to High-Pressure Processing (HPP) applications in ultra-processed meats. Our analysis reveals that HPP consumes 2.5–3.2 kWh/kg up to 26× more energy than thermal pasteurization primarily due to hydraulic system demands and adiabatic heat dissipation during batch cycling. Scalability limitations stem from batch-based processing (3–7 min/cycle), vessel size constraints (